Pelatihan Penggunaan Canva Dan AI Untuk Meningkatkan Efektivitas Pembelajaran Pada RA Nurul Hikmah - Frisma Handayanna; Andi Saryoko (AMMA : Jurnal Pengabdian Masyarakat, 2026)
This community service activity is motivated by the need to improve teacher competency in utilizing digital technology to support a more creative, interactive, and effective learning process. In today's digital era, the use of visual-based learning media and the use of artificial intelligence (AI) is very important, especially in early childhood education. However, there are still limitations in teacher knowledge and skills in using applications such as Canva and AI technology as learning media. The purpose of this activity is to improve teachers' abilities in designing attractive learning media using Canva and utilizing AI to help compile materials, learning ideas, and evaluations more efficiently. In addition, this activity aims to encourage learning innovation so that it can increase student engagement and understanding. The outputs generated from this activity include: (1) improving teacher skills in using Canva and AI, (2) creating creative digital-based learning media products, (3) compiling a simple module or guide to using Canva and AI in learning, and (4) improving the quality of the learning process to be more interactive and effective at RA Nurul Hikmah.